A Human Rights-Based Approach to Psychiatry: Is It Possible? - Emma Broberg; Agneta Persson; Anna Jacobson; Anna-Karin Engqvist (Harvard FXB Center for Health and Human Rights, 2020)
While it is becoming more common to hear calls for a human rights-based approach (HRBA) to health, documented efforts to apply the approach in practice remain scant. This paper presents a review of a pilot study applying an HRBA to psychiatric care in Gothenburg, Sweden. Based on the reflections of some involved in the pilot, and on the evaluation carried out, it presents the context, process, effects, and lessons learned. In the paper, we structure our experiences of an HRBA around the United Nations' guiding principles of dignity and empowerment, equality and non-discrimination, participation and inclusion, accountability, and transparency. We discuss challenges encountered during the project, such as realizing meaningful participation and challenging the hierarchies of different professions within care. We also discuss successes, such as contributing to an overall strategic goal to eliminate all coercive measures in psychiatric care. We then offer our reflections, as the core team involved in the pilot, on how to make an HRBA sustainable in a large organization and provide practical recommendations based on our experiences.